2022
DOI: 10.3389/fmicb.2022.916824
|View full text |Cite
|
Sign up to set email alerts
|

Early life administration of Bifidobacterium bifidum BD-1 alleviates long-term colitis by remodeling the gut microbiota and promoting intestinal barrier development

Abstract: Inflammatory bowel disease (IBD) is a chronic intestinal disease characterized by microbiota disturbance and intestinal mucosal damage. The current study aimed to investigate the preventive effects of Bifidobacterium bifidum BD-1 (BD-1) against long-term IBD and possible mechanism by which it alters the gut microbiota, immune response, and mucosal barrier. Our study found that early treatment of BD-1 + Ceftri (ceftriaxone followed by BD-1) and BD-1 confers a certain protective effect against the occurrence of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 54 publications
1
4
0
Order By: Relevance
“…SIgA is the main component of the mucosal defense system of the body and plays a decisive role in the first line of defense against diseases (Kumar et al, 2020;. Our present results showed that complex probiotics increased the SIgA level in the colon tissue, which was similar to the results of Peng C. et al (2022).…”
Section: Discussionsupporting
confidence: 85%
“…SIgA is the main component of the mucosal defense system of the body and plays a decisive role in the first line of defense against diseases (Kumar et al, 2020;. Our present results showed that complex probiotics increased the SIgA level in the colon tissue, which was similar to the results of Peng C. et al (2022).…”
Section: Discussionsupporting
confidence: 85%
“… Kim et al (2018) showed that Tregs balance in the colon may reduce symptoms of atopic dermatitis in mice, which is consistent with these results. In addition, butyrate intervention may alleviate inflammatory damage of colonic mucosa, which may be related to butyrate as an energy material of colon mucosa, strengthening the nutrition of colon mucosal cells and inhibiting local mucosal inflammation ( Zhang et al, 2021 ; Peng et al, 2022 ). The specific mechanism needs more in-depth research.…”
Section: Discussionmentioning
confidence: 99%
“…Representative probiotic supplements of Bifidobacterium spp. contain Bifidobacterium BLa80, Bifidobacterium longum CECT 7894, Bifidobacterium bifidum BD-1, Bifidobacterium bifidum H3-R2, Bifidobacterium bifidum H3-R2, among others [ 162 , 163 , 164 , 165 , 166 ]. Representative beneficial strains of Lactobacillaceae include Lactobacillus paracasei IJH-SONE68, Lactobacillus paracasei L9, Lactobacillus casei strain Shirota, Bifidobacterium lactis BL-99 and others [ 167 , 168 , 169 , 170 ] (shown in Table 4 ).…”
Section: Pharmacological Interventions For Ibd and Their Effects On G...mentioning
confidence: 99%